2017
DOI: 10.1055/s-0037-1603318
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Body Mass Index Specific Weight Gain Recommendations: Impact on Preterm Birth in Twin Pregnancies

Abstract: Objective To determine whether achievement of body mass index specific weight gain recommendations is associated with reduced preterm birth or neonatal morbidity among twin gestations. Study Design This was a retrospective cohort study of twin gestations delivered at the Medical University of South Carolina from 2000 to 2010. In total, 588 women in all prepregnancy body mass index categories who delivered ≥24 weeks' gestation were included. Women were grouped as achieved or underachieved based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…With respect to the birthweight of twins our results suggest that the rate of twins with a BW < 1500 g increased in parallel with increasing pre-pregnancy BMI and EGWG, which is in contrast to other results [8,36,47]. Pre-pregnancy maternal underweight and low maternal GWG are reported to be associated with higher rates of preterm birth, low BW or SGA and NICU admissions [37,[48][49][50][51][52]. In our cohort, the rate of underweight women did not change with time and thus can hardly explain the increasing rates of low BW and prematurity in twins.…”
Section: Meaning Of the Findingscontrasting
confidence: 74%
“…With respect to the birthweight of twins our results suggest that the rate of twins with a BW < 1500 g increased in parallel with increasing pre-pregnancy BMI and EGWG, which is in contrast to other results [8,36,47]. Pre-pregnancy maternal underweight and low maternal GWG are reported to be associated with higher rates of preterm birth, low BW or SGA and NICU admissions [37,[48][49][50][51][52]. In our cohort, the rate of underweight women did not change with time and thus can hardly explain the increasing rates of low BW and prematurity in twins.…”
Section: Meaning Of the Findingscontrasting
confidence: 74%
“…Pregnant women with AGWG had the lowest incidence of PTB in the three GWG groups, which indicated that very low or high GWG was likely to cause poor outcomes, consistent with previous studies. [33][34][35][36][37] Based on our findings, we emphasized the need for adequate GWG in women with twin pregnancies, as this can potentially reduce the burden of LBW and preterm birth. However, for pregnant women with GDM, while enhancing nutrition during pregnancy, strict weight management was needed to prevent excessive GWG.…”
Section: Discussionmentioning
confidence: 76%